Comparison of CE-FDG-PET/CT with CE-FDG-PET/MR in the evaluation of osseous metastases in breast cancer patients - Catalano, O A (Br J Cancer, 2015)
BACKGROUND: Despite improvements in treatments, metastatic breast cancer remains difficult to cure. Bones constitute the most common site of first-time recurrence, occurring in 40–75% of cases. Therefore, evaluation for possible osseous metastases is crucial. Technetium 99 ((99)Tc) bone scintigraphy and fluorodexossyglucose (FDG) positron emission tomography (PET)-computed tomography (PET-CT) are the most commonly used techniques to assess osseous metastasis. PET magnetic resonance (PET-MR) imaging is an innovative technique still under investigation. We compared the capability of PET-MR to that of same-day PET-CT to assess osseous metastases in patients with breast cancer. METHODS: One hundred and nine patients with breast cancer, who underwent same-day contrast enhanced (CE)-PET-CT and CE-PET-MR, were evaluated. CE-PET-CT and CE-PET-MR studies were interpreted by consensus by a radiologist and a nuclear medicine physician. Correlations with prior imaging and follow-up studies were used as the reference standard. Binomial confidence intervals and a χ(2) test were used for categorical data, and paired t-test was used for the SUVmax data; a non-informative prior Bayesian approach was used to estimate and compare the specificities. RESULTS: Osseous metastases affected 25 out 109 patients. Metastases were demonstrated by CE-PET-CT in 22 out of 25 patients (88%±7%), and by CE-PET-MR in 25 out of 25 patients (100%). CE-PET-CT revealed 90 osseous metastases and CE-PET-MR revealed 141 osseous metastases (P<0.001). The estimated sensitivity of CE-PET-CT and CE-PET-MR were 0.8519 and 0.9630, respectively. The estimated specificity for CE-FDG-PET-MR was 0.9884. The specificity of CE-PET-CT cannot be determined from patient-level data, because CE-PET-CT yielded a false-positive lesion in a patient who also had other, true metastases. CONCLUSIONS: CE-PET-MR detected a higher number of osseous metastases than did same-day CE-PET-CT, and was positive for 12% of the patients deemed osseous metastasis-negative on the basis of CE-PET-CT.